2017
DOI: 10.1002/ps.4610
|View full text |Cite
|
Sign up to set email alerts
|

Cyclohexylamine inexplicably induces antennae loss in Formosan subterranean termites (Coptotermes formosanus Shiraki): cyclohexylamine hydrogen phosphate salts are novel termiticides

Abstract: Cyclohexylamine appears to be a novel termiticide with a previously unreported mechanism of toxicity. Its hydrogen phosphate salts retain the toxic effect and are inexpensive and easily synthesized. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The shortest P-O bond is that whose O atom act as acceptor of two symmetric hydrogen bonds. Bonds and angles within the monocyclohexyl ammonium are otherwise comparable to those recorded in the literature [22][23][24]. and Figure 4).…”
Section: Resultssupporting
confidence: 83%
“…The shortest P-O bond is that whose O atom act as acceptor of two symmetric hydrogen bonds. Bonds and angles within the monocyclohexyl ammonium are otherwise comparable to those recorded in the literature [22][23][24]. and Figure 4).…”
Section: Resultssupporting
confidence: 83%
“…Furthermore, they also found that application of lufenuron inhibited the carcass-burying and particle transport behavior of the termites. Grimball et al (2017) described that cyclohexylamine is a novel termiticide, and its hydrogen phosphate salts maintain its toxicity. Bhatta et al (2016) tested the toxicity and repellency of spinosad and spinetoram against Coptotermes formosanus under laboratory conditions and reported that both insecticides exhibited toxicity and non-repellency against termites.…”
Section: Chemical Control Measuresmentioning
confidence: 99%
“…Grimball et al . (2017) described that cyclohexylamine is a novel termiticide, and its hydrogen phosphate salts maintain its toxicity. Bhatta et al .…”
Section: Chemical Control Measuresmentioning
confidence: 99%